2014
DOI: 10.3161/150811014x683381
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Occurrence of Bats (Chiroptera) on Islands in the North East Atlantic and on North Sea Installations

Abstract: The bats recorded from Iceland, the Faroe Islands, the Shetland Islands, the Orkney Islands, and North Sea installations are reviewed to the end of 2012. In total 12 species have been positively identified, while a considerable proportion of all records are sightings of unidentified bats. The largest number of species (8) has been recorded in Iceland, but the greatest number of individuals (180) has been found in Orkney. The most numerous species was Pipistrellus pipistrellus, which was only found in Orkney wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
(36 reference statements)
2
14
0
1
Order By: Relevance
“…There were no records in July until mid-August. The observed pattern of occurrence matches previous offshore monitoring studies in the German and Dutch North Sea (Hüppop & Hill 2016, Jonge Poerink et al 2013, Lagerveld et al 2014a, 2014b& 2015 and also corresponds to the findings of Boshamer & Bekker (2008), Petersen et al (2014) and Walter et al (2007).…”
Section: Spatiotemporal Occurrence Of Nathusius' Pipistrellesupporting
confidence: 90%
See 1 more Smart Citation
“…There were no records in July until mid-August. The observed pattern of occurrence matches previous offshore monitoring studies in the German and Dutch North Sea (Hüppop & Hill 2016, Jonge Poerink et al 2013, Lagerveld et al 2014a, 2014b& 2015 and also corresponds to the findings of Boshamer & Bekker (2008), Petersen et al (2014) and Walter et al (2007).…”
Section: Spatiotemporal Occurrence Of Nathusius' Pipistrellesupporting
confidence: 90%
“…Bats have also been observed during ship-based bird surveys in the North Sea and have been found on oil and gas platforms, ships and remote islands (Skiba et al 2007, Walter et al 2007, Boshamer and Bekker 2008, Petersen et al 2014. Recently a few ringing recoveries of Nathusius' pipistrelles (Pipistrellus nathusii) have shown that bats are able to cross the North Sea successfully 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Bats have also been observed during ship-based bird surveys in the North Sea and have been found on oil and gas platforms, ships and remote islands (Skiba et al 2007, Walter et al 2007, Boshamer & Bekker 2008, Petersen et al 2014. So far there have been eight recoveries of Nathusius' pipistrelles (Pipistrellus nathusii) which have shown that bats are able to cross the North Sea successfully.…”
mentioning
confidence: 99%
“…Bats even visit islands that are completely devoid of local bats, such as when the hoary bat, Lasiurus cinereus, visits small, treeless islands near the coast of California (Cryan and Brown 2007). There are also records of individual bats on islands far from their migratory pathways, probably as a result of strong winds pushing them off course (Petersen et al 2014). Some of these examples, however, might be the result of passive transport by humans, especially via ship cargoes (Constantine 2003;Petersen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are also records of individual bats on islands far from their migratory pathways, probably as a result of strong winds pushing them off course (Petersen et al 2014). Some of these examples, however, might be the result of passive transport by humans, especially via ship cargoes (Constantine 2003;Petersen et al 2014).…”
Section: Introductionmentioning
confidence: 99%